PENINGKATAN PERANAN LEMBAGA PERKREDITAN DESA (LPD) DALAM MEMBANGUN EKONOMI RAKYAT DI KECAMATAN DENPASAR BARAT - MURJANAYASA, I GST WAYAN (Buletin Udayana Mengabdi; Vol 7 No 1 (2008): Volume 7 No.1 – April 2008, 2012)
ABSTRACT In purpose to improve the knowledge of LPD’s stake holders, that include the chief of village association (Prajuru Desa Pakraman), local people, and entrepreneur about the role of LPD in order to empowering people’s economic is the reason of this public dedication. Training is held on Friday, 5st October 2007 which took place on the Meeting Room of Denpasar Barat subdistrict office, opened by subdistrict head of Denpasar Barat. This even is participated by management of village association, LPD’s management, small and medium scale business entrepreneur in Denpasar Barat District, with number 40 persons. This event is generally well handled where all audiences are showing the enthusiastic respond along the event due to the ambience is typically more like class session rather than the audience usually hare from government. The program also completed with discussion among the panelists and audience. As mentioned before, by this event the knowledge of LPD’s stake holders about the role of LPD in order empowering the people economic could be improved. So, the development in both sides, people economic an LPD’s performance will sustainable increased.